Experimento com leilões e avaliação de ativos pelo custo corrente para mensuração do capital intelectual: uma aplicação nas empresas Gama, GVDASA e SKA - Dameda, André das Neves (Universidade do Vale do Rio do Sinos, 2008)
Social and economical transformations witnessed since the end of the decade of 1970 had evidenced the importance of knowledge as an intangible economic resource and motivated both academic community and market to identify and measure this resource, also denominated intellectual capital. The objective of this study is to analyze the combined usage of auction experiments and current cost asset valuation as a procedure to measure intellectual capital. Relations among intangible assets, goodwill and intellectual capital were discussed, as well as the main measurement models. Based on the theoretical requirements of experimental economy, an experiment was designed and executed in the format of an auction, aiming to indicate the market value of the three enterprises compounding the sample. Later a valuation of the permanent assets was conducted through current cost, allocating an adjusted book value free from distortions inherent to the historical cost valuation. From the difference between indicated market value a
Keywords: avaliação de ativos; economia experimental; leilões; capital intelectual; asset valuation; auctions; experimental economy; intellectual capital; Ciências Sociais Aplicadas